(untitled) (International Journal of Biology and Chemistry, 2015)
In pharmacotherapy and prevention of “free radical diseases”, including diseases of the cardiovascular system, gastrointestinal tract, malignancies, herbal medicinal products become important, the effect of which is based on synergistic action of the major groups of natural compounds, such as polyphenols (mainly condensed tannins and flavonoids), amino, phenolic, polyene carboxylic acids, vitamins and minerals. Herbal substances of antioxidant action obtained on the basis of Kazakhstani plants are presented and described. The allocated herbal substances are notable by their bioavailability, low toxicity, absence of allergic reactions and cumulative effects, possibility of their long-term use for treatment and prevention of diseases.